2020
DOI: 10.1186/s12944-020-01341-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of dietary patterns with endocannabinoids levels in overweight and obese women

Abstract: Background: Higher levels of anandamide (AEA) and 2-arachidonoylglycerol (2-AG), the main arachidonic acidderived endocannabinoids, are frequently reported in overweight and obese individuals. Recently, endocannabinoids have become a research interest in obesity area regarding their role in food intake. The relationship between dietary patterns and endocannabinoids is poorly understood; therefore, this study evaluated the association of the dietary patterns with AEA and 2-AG levels in overweight and obese wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Numerous studies have found a positive association between circulating levels of endocannabinoids (AEA and/or 2-AG) and obesity in humans [10][11][12]. The elevated levels of endocannabinoids in human obesity are related to diet [13] and have been found to decrease after bariatric surgery [14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found a positive association between circulating levels of endocannabinoids (AEA and/or 2-AG) and obesity in humans [10][11][12]. The elevated levels of endocannabinoids in human obesity are related to diet [13] and have been found to decrease after bariatric surgery [14].…”
Section: Introductionmentioning
confidence: 99%
“… 85 And more recently close links have been made between dietary lipid intake and endocannabinoid levels in both males and females. 86 , 87 These results may account for the phenomenon commonly referred to as the ‘munchies,’ in which cannabinoid use is linked with an increase in food intake. Additionally, through interactions with the mesolimbic dopaminergic pathways, endocannabinoids promote the drive to seek high reward foods.…”
Section: The Endocannabinoid System: a Source Of Appetite Stimulationmentioning
confidence: 91%
“…A study by Yagin et al found that a Western dietary pattern was positively associated with circulating levels of 2-AG and AEA. Women with eating patterns in line with a healthy diet had lower levels of circulating eCB than those with eating patterns not in line with a healthy diet(101).…”
mentioning
confidence: 87%